Hofstede’s Cultural Dimensions in Mexican Literature - MUÑOZ-OROZCO, JAVIER (Sociedad y Economía, 2025)
This research is based on Hofstede’s work about Cultural Dimensions applied specifically to Mexican culture as it appears in the work of famous Mexican literature writers. The research made by Hofstede on 74 countries describe some traits that are common to these countries in different degrees, and serve as a basis for further studies regarding the particular and profound meaning that each country gives to that dimensions. In the case of this study an analysis is made of the three dimensions where Mexico scores highly: Power Distance, Masculinity and Indulgence. The research method is based on the analysis of Mexican literature and history due to the holistic and integrative character of these two disciplines. The findings corroborate greatly the high scores of these three dimensions, and give an explanation of their psychological meaning for Mexican people.